Elevated BEAN1 expression correlates with poor prognosis, immune evasion, and chemotherapy resistance in rectal adenocarcinoma - Shapaer, Tiannake; Chen, Yi; Pan, Yipeng; Wu, Zhimin; Tang, Tuoxian; Zhao, Zeliang; Zeng, Xiangyue (Discover. Oncology, 2024)
Background The BEAN1 gene, primarily studied in neurodegenerative diseases, has been scarcely studied in the context of cancers. Our research examines BEAN1 expression specifically in rectal adenocarcinoma (READ) and its association with prognosis, immune evasion, and chemotherapy resistance. Methods Data from TCGA and GEO were analyzed to assess BEAN1 levels across various cancer types, with particular emphasis on READ. Functional enrichment, immune infiltration, and treatment response analyses were conducted, followed by validation using patient tissue samples. Results READ tissues exhibited a marked increase in BEAN1 expression compared to normal tissues. Elevated BEAN1 levels were associated with reduced overall survival and increased immune suppression, characterized by elevated M2 macrophage infiltration and reduced CD8+ T cell presence. BEAN1 expression was also linked to higher immune checkpoint genes expression and resistance to immune checkpoint inhibitors and 5-fluorouracil. Conclusion This research offers initial evidence that BEAN1 is linked to unfavorable prognosis, immune escape, and resistance to chemotherapy in READ. BEAN1 appears to be a promising new biomarker and potential therapeutic target, warranting further investigation into its potential clinical applications in improving treatment outcomes for READ patients.